Conclusion: From recovery to renewal of the agrifood system - Boughton, Duncan; Minten, Bart (International Food Policy Research Institute, 2024)
Myanmar’s agrifood system is of critical importance for the near-term survival and longer-term flourishing of its diverse population. Prior to the recent crises, the food system accounted for almost half (47 percent) of Myanmar’s GDP and almost two-thirds (64 percent) of employment, while primary agriculture accounted for 22 percent of GDP and 49 percent of employment (Chapter 2). Recovery from the multiple crises Myanmar has faced since 2020 will require a combination of effective humanitarian assistance and sustained policy reforms and investment to resolve infrastructure limitations and constraints to sustainable productivity growth. These efforts are necessary to enable the agrifood system to fulfill its potential to improve food and nutrition security and reduce poverty.